Strategi Bank Indonesia dalam Mengakselerasi Ekonomi Syariah Melalui Program Pengembangan Kemandirian Ekonomi Pesantren - Riani, Deni Elva; Arisandy, Yosy; Hasibuan, Rahmat Putra Ahmad (Indonesian Journal of Islamic Economics and Business, 2024)
This study aims to analyze Bank Indonesia's strategy in accelerating Islamic economics through the economic independence development program for Islamic boarding schools (pesantren) in Bengkulu Province. The research method used is qualitative with a descriptive approach. The findings indicate that Bank Indonesia has successfully strengthened the role of pesantren in the halal product ecosystem by providing support in the form of training, production equipment, and marketing. The pesantren involved have successfully developed their business units. This program has also improved Islamic financial literacy among pesantren and students, while providing entrepreneurial skills. The implications of this study highlight the importance of collaboration between Bank Indonesia, pesantren, and strategic partners to accelerate the development of Islamic economics. This research offers new insights by emphasizing the role of pesantren in the development of Islamic economics at the local level, which can contribute to the national economy.